PENINGKATAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL BAMBOO DANCING DALAM PEMBELAJARAN PKn DI KELAS IV SDN 05BIRUGO BUKITTINGGI - Arman, Andri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research based on the fact found at SDN-05-Birugo-Bukittinggi that Civic Learning inIV Class was mostly still conventional and also, the teacher usually came self-centered in learning process so the result of student’s studying has not been as appropriate as what has expected. Therefore, the research uses bamboo-dancing method whichaims for improving Civic studying process in IV Class at SDN-05-Biruggo-Bukittinggi. This is Research of Classes Action type of research, using qualitative and quantitative method. The outcome of this research shows achievement that: results of students’ studying for cycle I in first and second meeting are 62 and 72 in average and it’s considered to increase until 80 to 88 in cycle II. Kata Kunci : model bamboo dancing, hasil belajar